2019
DOI: 10.1101/572628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COI metabarcoding primer choice affects richness and recovery of indicator taxa in freshwater systems

Abstract: DNA-based biodiversity analysis has gained major attention due to the use of high throughput sequencing technology in approaches such as mixed community or environmental DNA metabarcoding. Many cytochrome c oxidase subunit I (COI) primer sets are now available for such work. The purpose of this study is to look at how COI primer choice affects the recovery of arthropod richness, beta diversity, and recovery of site indicator taxa in benthos kick-net samples typically used in freshwater biomonitoring. We examin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…Though the overall percentage of retained raw arthropod reads is low, it is consistent with previous work from bulk samples that are known to comprise a phylogenetically diverse mixture of taxa that are detected even when using primers originally developed to target arthropods. 15,16 Since only a proportion of arthropod ESVs could be identified with confidence, we present our results at the ESV rank wherever possible (Fig S3). Rarefaction curves show that we saturated the sequencing of our arthropod COI PCR products (Fig S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the overall percentage of retained raw arthropod reads is low, it is consistent with previous work from bulk samples that are known to comprise a phylogenetically diverse mixture of taxa that are detected even when using primers originally developed to target arthropods. 15,16 Since only a proportion of arthropod ESVs could be identified with confidence, we present our results at the ESV rank wherever possible (Fig S3). Rarefaction curves show that we saturated the sequencing of our arthropod COI PCR products (Fig S4).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with a previous study that showed how COI metabarcoding may actually recover a greater taxonomic diversity of site indicators in addition to the usual expected bioindicators. 15 Future studies should attempt to pair soil arthropod metabarcoding with local DNA barcoding to improve taxonomic assignment rates. Despite this, the use of soil arthropod metarbarcodes as site bioindicators was successful and samples from two similar jack pine stands with different origins were distinguished from each other based on beta diversity and the presence of site indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Marquina et al 2018). These results were also recently confirmed by (Hajibabaei et al 2019a), which 411 showed that the use of multiple primer sets did not substantially improve taxa detection. Conclusions 415 Our study demonstrates that the fwh2, BF1/2/3 + BR2 and mlCOIintF based primer sets all 416 perform well when metabarcoding terrestrial arthropod samples.…”
mentioning
confidence: 58%
“…Marquina et al 2018). These results were also recently confirmed by (Hajibabaei et al 2019a), which 411 showed that the use of multiple primer sets did not substantially improve taxa detection. Conclusions 415 Our study demonstrates that the fwh2, BF1/2/3 + BR2 and mlCOIintF based primer sets all 416 perform well when metabarcoding terrestrial arthropod samples.…”
mentioning
confidence: 58%